2001
DOI: 10.1039/b104784c
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A continuum source atomic absorption spectrometry (CS-AAS) instrument consisting of a high-resolution echelle spectrometer and a two dimensional charge coupled device (2D-CCD) with a high frame rate was used to measure intensities as a function of height and time in the graphite furnace. The image of the furnace was reduced to a height less than that of the entrance slit to allow the full vertical profile of the furnace to be viewed. Spatially resolved absorbance, A SR , was computed as the average of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This expected gradient is the normal gradient and has been observed, with varying degrees of intensity, for all elements that interact with the carbon wall (i.e., Al, Cu, Cr, and Pb in ref. 20 and Al, Co, Mn, and Pd in ref. 17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This expected gradient is the normal gradient and has been observed, with varying degrees of intensity, for all elements that interact with the carbon wall (i.e., Al, Cu, Cr, and Pb in ref. 20 and Al, Co, Mn, and Pd in ref. 17).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup has been described previously. 20 It consists of a 300 W xenon arc lamp with an integral parabolic reflector (Cermax LX300UV, ILC Technology, Sunnyvale, CA, USA), a longitudinally heated graphite furnace (PerkinElmer Corporation, HGA 500, Norwalk, CT, USA), an autosampler (PerkinElmer, AS-72), an echelle polychromator (SpectraSpan V, Spectrametrics Inc., now out of business), a 2D-CCD camera (PixelVision, Beaverton, OR, USA) mounted on x-y-z-W-stage (three dimensions and angle of rotation), a ''SpectraVideo'' controller (PixelVision), and a 200 MHz Pentium computer. The 2D-CCD camera is an 86 6 80 pixel (height by width), back-illuminated, split-frame transfer device.…”
Section: Experimental Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Harnly and co-workers 193,194 continue to publish interesting data from their work on spatially resolved ETAAS using a continuum source. It was observed that photometric errors induced by analyte non-homogeneity across the furnace were greatest for platform atomization when the full furnace image was viewed and for either platform or wall atomization when a 2 mm sub-section of the furnace was viewed.…”
Section: Electrothermal Vaporisationmentioning
confidence: 99%